The application of the infrared thermography on titanium alloy for studying fatigue behavior (Fracture and Structural Integrity, 2013)
The infrared thermography is an attractive tool for studying the fatigue behavior of materials. Basedon two theoretical models of fatigue damage indicators, this work studied the fatigue properties of the virgin Ti-6Al-4V alloy. According to the two damage indicators and the energy theory, the relationship between themacro-phenomenon and the micro-structural evolution during fatigue process was discussed. The fatigue limitof the titanium alloy was rapidly determined based on the measured temperature increment signals. Thecapability of the infrared thermographic method on the evaluation of fatigue properties was validated.
Keywords: Thermography